2015
DOI: 10.1007/s00424-015-1727-z
|View full text |Cite
|
Sign up to set email alerts
|

UCP2 modulates single-channel properties of a MCU-dependent Ca2+ inward current in mitochondria

Abstract: The mitochondrial Ca2+ uniporter is a highly Ca2+-selective protein complex that consists of the pore-forming mitochondrial Ca2+ uniporter protein (MCU), the scaffolding essential MCU regulator (EMRE), and mitochondrial calcium uptake 1 and 2 (MICU1/2), which negatively regulate mitochondrial Ca2+ uptake. We have previously reported that uncoupling proteins 2 and 3 (UCP2/3) are also engaged in the activity of mitochondrial Ca2+ uptake under certain conditions, while the mechanism by which UCP2/3 facilitates mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…Uncoupling protein 2 (UCP2) polymorphisms have been associated with altered risk of insulin resistance (9). Since UCP2 has been shown to regulate MCU activity in HeLa cells and cardiomyocytes (5,30), it will be very interesting to determine whether UCP2 modulates MCU calcium current also in adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Uncoupling protein 2 (UCP2) polymorphisms have been associated with altered risk of insulin resistance (9). Since UCP2 has been shown to regulate MCU activity in HeLa cells and cardiomyocytes (5,30), it will be very interesting to determine whether UCP2 modulates MCU calcium current also in adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The latter study showed that UCP4 attenuates mitochondrial Ca 2+ accumulation and oxidative stress, which contributes to neuroprotection. One mechanism by which UCPs may regulate mitochondrial Ca 2+ dynamics is by interacting with the mitochondrial Ca 2+ uniporter, as suggested by experiments showing that UCP2 increases uniporter Ca 2+ currents [50]. In addition to affects on cellular Ca 2+ signaling, neuronal UCPs may also influence other prominent signaling pathways including the cyclic AMP pathway.…”
Section: Mitochondrial Uncoupling Proteins and Neuroprotectionmentioning
confidence: 99%
“…The mitochondrial protein UCP2 was shown to modulate MCU function negatively, and therefore, implicated to influence cardiac cytosolic Ca 2+ handling (Trenker et al 2007;Hoppe, 2010;Waldeck-Weiermair et al 2010bBondarenko et al 2015;Motloch et al 2015bMotloch et al , 2016b. However, the amplitude of cytosolic Ca 2+ transients was not altered in Ucp2 −/− mice (Motloch et al 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial Ca 2+ uptake is mostly driven by the mitochondrial calcium uniporter (MCU; Kirichok et al 2004;Michels et al 2009;Hoppe, 2010;Bondarenko et al 2013Bondarenko et al , 2014Waldeck-Weiermair et al 2015). Cardiac UCP isoforms were shown to modulate MCU function and, for this reason, suggested to influence cytosolic Ca 2+ handling (Trenker et al 2007;Hoppe, 2010;Waldeck-Weiermair et al 2010a,b, 2013De Marchi et al 2011;Bondarenko et al 2015;Motloch et al 2015bMotloch et al , 2016aMadreiter-Sokolowski et al 2016). Accordingly, Ucp2 knockout (Ucp2 −/− ) mice were demonstrated to exhibit decreased MCU activity and, therefore, a reduced mitochondrial Ca 2+ uptake (Trenker et al 2007;Motloch et al 2016b).…”
Section: Introductionmentioning
confidence: 99%